From microbes to farmers perspectives: enhancing soil health through on-farm sustainable agricultural practices - Bonini Pires, Carlos Augusto (Kansas State University, 2023)
One of the pivotal challenges for ensuring the sustainability and resiliency of agroecosystems is the selection of agricultural practices that can effectively nurture soil health and maintain productivity levels. In this scenario, regenerative agriculture practices, such as cover crops, can offer multiple benefits to soils by improving soil health and sustaining the soil microbial community structure and activity. The overall goal of this research was to explore on-farm sustainable agricultural practices to design farming systems for sustaining soil health management in Kansas. The objective was to quantify the impact of cover crops and nutrient management on biological, chemical, and physical soil health indicators at the farm level. Besides soil nutrients, selected indicators included phospholipid fatty acids, enzyme activity, soil organic carbon, potentially mineralizable nitrogen, and water-stable aggregates. Additionally, farmers’ perspectives were assessed regarding collaborative on-farm research and incorporate farmer input and collaboration to enhance the effectiveness of these practices in “real-world” agricultural settings. Overall, cover crops improved soil health by increasing soil microbial biomass, bacteria, fungi, [beta]-glucosidase activity, soil organic carbon and other biological soil health indicators. The extent of these changes occurred in response to the precipitation patterns across sites. Our findings support the hypothesis that increasing soil organic carbon levels and stimulating soil microbial growth and activity under water-limited environments requires time. Besides increasing several biological soil health indicators, cover crops improved aggregate stability. The continuous presence of living roots from cover crops significantly impacted the development and maintenance of macroaggregates as affected by increased fungi and bacterial communities. Maintaining and increasing soil organic carbon (e.g., soil organic matter) is considered an essential strategy to improve N management. Our study indicated that after 25 years of regenerative agriculture practices, in the field conditions of the study, decreasing the N rate by 48% for winter wheat production is feasible without compromising yields and soil organic carbon levels in the short term. However, reducing the N rate would not be advisable for corn production as it may lead to economic losses. This approach can empower farmers to take advantage of the mineralized N from the soil they built over time and use external inputs more efficiently, ultimately promoting soil health. Finally, our research survey demonstrated that farmers’ high trust in on-farm research outcomes can influence the adoption of sustainable practices. Limitations like time management and plot setup were identified in on-farm research, while strengths included practical knowledge gained and unbiased insights. Notably, a shift towards conservation practices has been made in the last ten years, with cover crops and no-till at the forefront of these changes. Farmers were 40% more likely to adopt practices supported by findings of on-farm research compared to off-farm ones, and farmers’ primary motivators for doing on-farm research were productivity and profitability. Insights of this nature have implications for fostering collaborations, addressing constraints, and maximizing the impact of on-farm research, offering guidance for sustainable agriculture progress in the U.S. and beyond. Results from this research survey can drive further policy and initiatives promoting on-farm research. Ultimately, the diverse scientific methods employed in this work, from laboratory-based analysis to on-farm research and nationwide survey, significantly contributed to advancing the scientific understanding of how agricultural practices impact soil-crop outcomes and how farmers' perspectives about on-farm research impact their decision-making. Overall, this research offered a strong foundation for practical applications that can contribute to developing more resource-efficient, profitable, resilient, and healthy agricultural systems. This research can potentially guide farmers and land managers in optimizing their farming strategies for a more sustainable future in agriculture.
Keywords: Soil health; On-farm; Soil microbiology; Sustainability; Nutrient management; Cover crops